Medication adherence: a review of policy and education in South Africa - Nyoni, Cynthia Nomagugu (Rhodes University, Faculty of Pharmacy, Pharmacy)
Medication adherence is a patient's active and voluntary participation in following all the recommendations and instructions agreed upon with a health care provider such as a pharmacist. Adherence is a multidimensional phenomenon determined by the interplay of five factors: patient-related factors, socioeconomic factors, condition-related factors, health system-related factors, and therapy-related factors. Medication non-adherence is a problem in many countries, especially low to middle-income countries, including South Africa (SA). In low to middle-income countries, non-adherence is often worse due to insufficient health resources and inequities in access to health care. Medication adherence is a global problem and has raised the need for research and review. Many healthcare professionals, especially pharmacists, have an essential role in promoting medication adherence. This study described, explained and evaluated the policies in SA relating to the pharmacist's role in promoting medication adherence. Furthermore, it described medication adherence-related education at four universities in South Africa. The study was qualitative, and a two-phased approach was employed. In the first phase, a document analysis of the pharmacist's role in supporting medication adherence was conducted as described in national policies and guidelines in SA. A total of 38 documents were analysed, including critical documents such as the South African Pharmacy Council Good Pharmacy Practice Manual and Associated SAPC rules (GPP) manual, National Drug Policy (NDP), Standard treatment guidelines (STGS) and Integrated Adherence Guidelines. The READ approach was used in conducting the document analysis and involved (1) preparing materials, (2) extracting data, (3) analysing data, and (4) distilling findings. The critical roles of pharmacists in medication adherence that were identified were in drug use, supply and management, dispensing, therapeutic drug monitoring, pharmacovigilance, pharmaceutical care, and special programmes like antimicrobial stewardship (AMS), multi-drug resistant tuberculosis (MDR-TB) care and antiretroviral treatment (ARV) and chronic conditions. In the second phase, in-depth interviews were conducted with lecturers to investigate and report on the inclusion of medication adherence and the teaching thereof in the curriculum of the Bachelor of Pharmacy Degree (BPharm) in pharmacy institutions in SA. Purposive sampling was used, and seven lecturers from four different institutions participated in the interviews. The interviews were conducted via ZoomÂ® and were transcribed and analysed using thematic analysis. The teaching of medication adherence in the BPharm curriculum of the respective interviewed pharmacy institutions was explored. It was found that the topic of medication adherence was integrated into all subjects throughout the curriculum and not taught as a formal course. Although medication adherence is taught in many disciplines, it is predominantly in pharmacy practice in all institutions. The teaching methods identified included lectures, case studies, workshops, tutorials, practicals, readings, tasks, assignments and videos. The perceived effectiveness of the teaching methods was explored; also the time spent teaching medication adherence and the time efficiency. Student understanding, interest and engagement with the topic were explored and determined through their assessment performance and class attendance. In conclusion, from policies, the pharmacist's role concerning adherence is indirectly integrated into many other roles. It is often not distinguishable from that of other healthcare professionals and is often implied as part of a more generic role. Pharmacy students are educated on medication adherence and the skills and knowledge required to identify, monitor and support patient adherence to therapy. However, there is scope to increase the course content on medication adherence. There is a need to identify effective strategies for preparing pharmacists to assist patients in medication adherence.
Keywords: Patient compliance -- South Africa; Drugs Administration-- Study and teaching (Higher); Pharmacist and patient -- South Africa; Pharmaceutical policy -- South Africa; Patient education -- South Africa; Medication adherence